Recent Advances in Laser as an Adjunctive Periodontal Therapy - Jagadeesan, Monika; Devi, S. Sakthi; Ramalingam, Kurinchichelvan; Kumar, R. Saravana; Srinivasan, K.; Rajalakshmi, H. (Achievements and Challenges of Medicine and Medical Science Vol. 3, 2024)
Since laser applications have been used in practically all dental specialties for more than 20 years their use in dentistry is not a novel approach. They can be used as a diagnostic tool to detect caries and subgingival calculus, as a cutting tool for hard dental tissues and as a disinfectant for root canals. Lasers can treat both soft and hard tissues, Calculus removal (erbium yttrium scandium gallium garnet and erbium yttrium aluminum garnet lasers), bio-stimulating root and implant surfaces, incision and ablation, osseous surgery, soft tissue excision, and bacterial reduction, are the various applications used in periodontology. Moreover their high sources of light, or more specifically non-ionizing, electromagnetic radiation, include lasers. The wavelengths of laser radiation are well-defined and predictable, and indeed the radiation seems to be more powerful at these wavelengths than can be produced by traditional light sources. Sutures are rarely indicated, there is very little possibility of mechanical trauma, and there is little scarring caused by lasers. The high proportion of patient acceptance of laser dentistry is one of its great advantages. Today’s patients are aware of lasers' benefits and today's dental lasers are portable, lightweight, compact, and becoming ever more accessible. Considering lasers used in dentistry, the prognosis seems optimistic. Practitioners can benefit from this new technology by knowing further about lasers and this form of light's attributes.